Ketidakadilan Gender terhadap Tokoh Utama Arte dalam Anime Arte karya Kei Ohkobu - Yulia Afifah Andriani (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This thesis is titled "Gender injustice against the main character of Arte in the Arte Anime by Kei Ohkubo". This study aims to analyze the form of gender injustice as well as the efforts made in enforcing the existence of women. The method used is a literature study, using the theory of gender injustice by Fakih and the theory of existentialist feminism by Beauvoir. The results of the analysis suggest that gender injustices, such as marginalization, can be countered by upholding individual freedoms to prove that women are capable of working on a par with men. Psychic violence, experienced by the main character, is overcome by rejecting the concept of "liyan". Other forms of injustice, such as subordination and workload, are fought by being a persistent intellectual figure. In addition, gender stereotypes that limit women are also broken through the role of women in social transformation